2021
DOI: 10.25115/eea.v39i4.4484
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Outbreak: An Analysis of Malaysian Household Income Class During Movement Control Order (MCO)

Abstract: The outbreak of COVID-19 has caused the Malaysian Government to take several steps towards the implementation of Movement Control Order (MCO). According to Bank Negara Malaysia, the implementation of MCO affects the national income with the estimated economic growth of Malaysia in 2020 which is expected to be around -2% to 0.5%. The effects of MCO due to COVID-19 not only affects the macro level but at micro level as well, especially those group of households. The group of households were expected to face high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…This group has the potential of experiencing significant financial downturn during the pandemic [38] while they also know that they were not being prioritized as a group that require financial empowerment by the authority. As mentioned previously, the authorities tend to prioritize the lower-class group in delivering any form empowerment initiative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This group has the potential of experiencing significant financial downturn during the pandemic [38] while they also know that they were not being prioritized as a group that require financial empowerment by the authority. As mentioned previously, the authorities tend to prioritize the lower-class group in delivering any form empowerment initiative.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, financial empowerment efforts were given by the authorities based on the statistic of how much individuals made per year; in the Malaysian context, the government and non-governmental organisations (NGO) focused their financial empowerment effort on the B40 group, the 40% of the population with the lowest financial input apart from those with physical disabilities [37]. This situation could be based on the perspective that individuals with lower income had expressed the highest need for empowerment, although it was reported that the M40 group (the 40% middle-class population) are facing a severe potential of a financial downturn due to the COVID-19 outbreak [38] and the overspending during the pandemic occurred at all financial layers of the society [39].…”
mentioning
confidence: 99%
“…► Pregnant women whose permanent residence is in the Anuradhapura district and had not planned to leave the district until childbirth. ► Period of amenorrhoea/gestational age is less than 13 weeks by the time of recruitment. Pregnant women with uncertain due dates and those who planned to leave the study setting for delivery were excluded from the study.…”
Section: Study Population and Samplementioning
confidence: 99%
“…Few studies have cited the adverse impact of the COVID-19 pandemic on the household economy 6 8. These studies investigated the adverse effects on household economies in Nigeria,12 changes in consumption patterns of Malaysian households,13 losing jobs and declining household income in some Asia-Pacific countries—Cambodia, the Lao People’s Democratic Republic, Malaysia, Indonesia, the Philippines, Myanmar, Thailand and Vietnam 14. Economic burden during COVID-19 could be more problematic for households of pregnant women, since pregnancy expenditure was already a burden in many low-income and middle-income countries 15.…”
Section: Introductionmentioning
confidence: 99%
“…While MCOs were intended to slow the spread of COVID-19, they had concerning impacts on socioeconomics and health. Low-income groups, particularly the bottom 40% of the economic spectrum known as the B40 in Malaysia, were most affected due to insufficient savings ( 6 ). Quarantine lockdowns and movement restrictions may have also exacerbated the root factors that lead to obesity and other risks and management of noncommunicable diseases (NCDs) ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%